THE INVESTIGATION LOOKS AT CHEST INJURIES RESULTING FROM BLUNT TRAUMA THROUGH A PROSPECTIVE AUTOPSY ANALYSIS A SINGLE-CENTER STUDY - KHAN , Z; KHAN , AM; BASIT , A; KHAN , AM; ALI , A (Biological and Clinical Sciences Research Journal, 2023)
Chest trauma is a significant public health concern, accounting for 15-20% of all trauma-related deaths. The purpose of this study was to examine chest injuries resulting from blunt trauma, with a focus on autopsies. The study aimed to evaluate the epidemiological characteristics of the victims, including their age, gender, and the type of trauma they experienced, as well as identify the leading causes of mortality in these cases. The study was conducted at the Department of Medicine at MTI, LRH, from March 2020 to March 2021 and examined 112 blunt trauma patients. The study collected comprehensive epidemiological data on the victims, including their age, gender, type of trauma, injuries, and other relevant case-related factors. A thorough form was created to record the historical and epidemiological data systematically. The study carefully examined every deceased person, including both external and internal injuries, as well as a detailed evaluation of the thoracic region's bones and joints. The average age of the victims was 31.7±5.41 years, with 16 (14.3%) in the age range of 1-20 years, 62 (55.5%) in the age range of 21-40 years, 18 (16.1%) in the age range of 41-60 years, and 16 (14.3%) in the age range of over 60 years. Of the 112 cases examined, 80 (71.4%) were related to road traffic accidents, 14 (12.5%) were falls from height, 12 (10.7%) were assaults, and 6 (5.4%) were miscellaneous incidents. Male victims constituted 92 (82.1%) of the cases, while female victims were 20 (17.9%). Motorcycles were the most common type of vehicle involved in road traffic accidents, accounting for 72 (64.3%) of the cases. In most cases, the survival rate was less than six hours, with 76 (67.9%) cases falling into this category. The primary causes of death were shock and bleeding, followed by suffocation and coma. In conclusion, the study found that road traffic accidents were the most common cause of chest injuries, likely due to the prevalence of automobiles. Shock and bleeding were the leading causes of death, followed by suffocation and unconsciousness. Most victims had a survival rate of less than six hours.